Acting Transnationally. A Case from Lisbon's Housing Social Movement in Time of Pandemic - Gori, Antonio (PARTECIPAZIONE E CONFLITTO, 2023)
With the changes and limitations due to the pandemic, social movements for housing rights readjust their activities and experiment with new practices. This short story aims to narrate how, through cooperation with groups in other countries, a collective in Lisbon reformulates its activities and achieves unprecedented results. I will tell how the Habita! association began working on new popular advocacy strategies, and how it managed to appeal to UN Committee on Economic, Social and Cultural Rights in order to avoid evictions of vulnerable subjects and force local governments to offer housing solutions.